Workshop: Priority Setting for Nationally Determined Contributions (NDC) - Implementation Plan in Rice Production - International Rice Research Institute (2021)
26 March 2021, Ha Noi, Vietnam — the Ministry of Agriculture and Rural Development (MARD) held the first workshop in support of planning the implementation of Vietnam's Nationally Determined Contribution (NDC) in the rice sector. Aiming at setting priorities for NDC implementation in rice production, the workshop highlighted different NDC scenarios to reduce greenhouse gas (GHG) emissions while gaining economic, social, and environmental benefits sustainably.